1996
DOI: 10.1172/jci118499
|View full text |Cite
|
Sign up to set email alerts
|

Impaired actions of insulin-like growth factor 1 on protein Synthesis and degradation in skeletal muscle of rats with chronic renal failure. Evidence for a postreceptor defect.

Abstract: The actions of insulin-like growth factor 1 (IGF-1) on protein turnover and of the IGF-1 receptor (IGF-1R) were examined in skeletal muscle of rats with chronic renal failure (CRF) and sham operated (SO), pair-fed controls. Acidemia was prevented in CRF rats with NaHCO 3 . Serum IGF-1 and skeletal muscle IGF-1 and IGF-1 mRNA were reduced in CRF rats. Dose-response studies revealed impaired stimulation of protein synthesis and suppressed inhibition of protein degradation by IGF-1 in epitrochlearis muscle of CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
129
3
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 49 publications
3
129
3
1
Order By: Relevance
“…Since IGF-I has been reported to inhibit MAFbx expression in the muscles of fasting and diabetic rats (Dehoux et al 2004), the increase in IGF-I in the muscle of arthritic rats should be followed by a decrease in muscular MuRF-1 and MAFbx gene expression. Since this is not the case, there is a possibility that arthritic muscles have become resistant to IGF-I, as has been observed in experimental models of sepsis (Fang et al 2000) and chronic renal failure (Ding et al 1996). This effect can be exerted by muscular TNF-a, since this cytokine acts on muscle cells inducing a state of IGF-I receptor resistance (Broussard et al 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Since IGF-I has been reported to inhibit MAFbx expression in the muscles of fasting and diabetic rats (Dehoux et al 2004), the increase in IGF-I in the muscle of arthritic rats should be followed by a decrease in muscular MuRF-1 and MAFbx gene expression. Since this is not the case, there is a possibility that arthritic muscles have become resistant to IGF-I, as has been observed in experimental models of sepsis (Fang et al 2000) and chronic renal failure (Ding et al 1996). This effect can be exerted by muscular TNF-a, since this cytokine acts on muscle cells inducing a state of IGF-I receptor resistance (Broussard et al 2003).…”
Section: Discussionmentioning
confidence: 98%
“…A study of uremic rats showed a reduction in GHR density in tibial growth plate [58] and low levels of mRNA for hepatic GH receptor [59]. In addition, there is evidence from animal studies that IGF-I resistance also arises from tissue insensitivity caused by a post-receptor defect in IGF-I-mediated signal transduction [60], although the site of the abnormality is controversial [61]. Ding et al [60] studied IGF-IR isolated from skeletal muscle of rats with CRF and reported an increase in IGF-IR number and a decrease in IGF-Iactivated receptor autophosphorylation and tyrosine kinase activity that could not be attributed to IGFBP activity.…”
Section: Gh-igf-i Insensitivity and Growth Failure In Ckdmentioning
confidence: 99%
“…Treatment with recombinant GH can, in part, overcome this resistant state [4]. Furthermore, there is a suggestion that there may also be IGF-I resistance in CKD that additionally contributes to the pathogenesis of growth retardation [5,6]. Perturbations in hypothalamic signaling pathways involving leptin and ghrelin, a ligand of the GH secretagogue receptor, may contribute to cachexia and wasting in CKD [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these findings there is evidence of a resistance to GH and IGF-I occurring in uremic muscle. Indeed, a reduced IGF-I and IGF-I mRNA, and a decreased IGF-I receptor tyrosine kinase activity have been observed in muscle from uremic rats (8,9).…”
Section: Introductionmentioning
confidence: 99%